2018
DOI: 10.1111/cpr.12459
|View full text |Cite
|
Sign up to set email alerts
|

KDM1A regulated the osteo/dentinogenic differentiation process of the stem cells of the apical papilla via binding with PLOD2

Abstract: KDM1A might have different role in different stages of osteo/dentinogenic differentiation process by binding partner with PLOD2, and finally resulted in the inhibited function for the osteo/dentinogenesis in SCAPs. Our studies provided a further understanding of the regulatory mechanisms of dynamic osteo/dentinogenic differentiation process in dental tissue MSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Then the gel was stained and cut for protein mass spectrometry analysis. The detailed procedures refer to our previous research [53].…”
Section: Protein Mass Spectrometrymentioning
confidence: 99%
“…Then the gel was stained and cut for protein mass spectrometry analysis. The detailed procedures refer to our previous research [53].…”
Section: Protein Mass Spectrometrymentioning
confidence: 99%
“…It was reported that KDM1A in SCAP regulatory mechanisms of dynamic osteo/dentinogenic differentiation showed more diverse outcomes when applied in vitro than in vivo. However, in the final outcome of KDM1A inhibition, it promoted osteo/dentinogenesis in vivo [123]. Moreover, H2S proved to aid in the differentiation of DPSCs and dentin formation in vitro and in vivo via Ca 2+ homeostasis and Ca 2+ influx/GSK3β/(glycogen synthase kinase-3β) β-catenin cascade response.…”
Section: Signaling Moleculesmentioning
confidence: 99%
“…The protein extraction and the gel electrophoresis tests were performed as previously described (Ge et al, 2014;Lv et al, 2016;Wang et al, 2018 2.5 | Alkaline phosphatase (ALP) activity assay and alizarin red detection SCAPs were cultured in mineralization-inducing medium (100 µM/ml ascorbic acid, 2 mM β-glycerophosphate, 1.8 mM KH 2 PO 4 and 10 nM dexamethasone). The ALP activity assay and Alizarin red detection were performed as previously described (Ge et al, 2014;Lv et al, 2016;Wang et al, 2018).…”
Section: The Western Blotmentioning
confidence: 99%
“…MSCs (Wang et al, 2018). Another study reported that KDM1A could also repress RUNX2 via H3K4me1 demethylation in myoblasts (Munehira, Yang, & Gozani, 2017).…”
Section: Kdm1a Inhibited the Migration And Chemotaxis Abilities Of mentioning
confidence: 99%